تطبيقات معياري القصدية والمقبولية في النص في معهود الخطاب عند العرب - الكنج، عثمان جميل قاسم (الجامعة الإسلامية العالمية, 2015)
This research at focusing on the issues of contemporary standards of textuality in the realm of Arabic tradition and its precedence in dealing with the issues of text and its standards. It also explains the contributions of the traditional Arab scholars in the field of text linguistics. This theoretical and conceptual framework will be employed in analyzing the book of Abu ‘Ubaydah: Kitab Ayyam al-‘Arab qabla al-islam (The Book of the History of the Arabs before Islam) in the context of intentionality and acceptability.The theoretical framework was applied in analyzing the discourse of text from the book in light of intentionality and acceptability. The study adapted two research approaches: first, the descriptive approach by which the researcher addressed the intentionality and acceptability notions in ancient Arab heritage as well as with contemporary linguists. Second, the analytic approach through which text from the book was selected and analyzed in light of intentionality and acceptability. The study concluded that contemporary linguists treat the standard of intentionality through the speech act theory under what is known as illocutionary and perlocutionary acts while treating the concepts of intentionality while discussing the explanation, rhetoric, and the effects of structures on intentionality as well as word and meaning.
يهدف البحث إلى إسقاط قضايا معايير النصية المعاصرة على التراث العربي القديم، أسبقيته في قضايا النصية ومعاييرها؛ وبيان إسهامات العلماء العرب القدامى في مجال اللسانيات النصية، ثم استثمار الإطار النظري والمفاهيمي في تحليل نص من كتاب أبي عبيدة كتاب أيام العرب قبل الإسلام في ضوء معيار القصدية والمقبولية، ويقوم البحث على المنهج الوصفي المنهج التحليلي. توصلت الدراسة إلى أن المحدثين اهتموا بمعيار القصدية عبر عنايتهم بنظرية الأفعال الكلامية، تحت ما يعرف بالخبر والإنشاء، وتطرقوا إلى مفاهيم القصدية في معرض حديثهم عن البيان، والبلاغة، وأثر التركيب في القصدية، واللفظ والمعنى، وأما المقاصد الظاهرة والخفية فقد تناولوها تحت بما يعرف ب: (المعنى) و(معنى المعنى)، وهو ما يمثل المقاصد الخفية، وما يعرف ب(الملاحن)، وهو في اللغة إمالة الكلام عن مقصده الظاهر إلى مقصد متخف، واهتم أصحاب نظرية التلقي بالقارئ بوصفه الطرف الثاني في العملية الإبداعية، تمثلت مفاهيم المقبولية عند البلاغيين، عبر المشاركة الإبداعية؛ أما أفق التوقع فقد ظهر لدى العرب القدامى عبر ما كانوا يتوقعونه للشعر استنادا إلى ما يتحصل عندهم من المعرفة الأولية لمعنى الأبيات، ومنهم من اهتم بالقارئ الأعلى الذي نجده عند ابن قتيبة، والقارئ المقصود الذي نجده جليا عند الجاحظ، ومنهم من اهتم بهيئة المتكلم ومكانته لما لها من أثر بالغ الأهمية في استجابة المتلقي وتفاعله مع الكلام.
792015
Keywords: التراث العربي -- الخطاب العربي -- التحليل اللغوي -- التناص